Effect of metakaolin developed from natural material Soorh on fresh and hardened properties of self-compacting concrete - Saand, A. (Springer Science and Business Media Deutschland GmbH, 2021)
This study describes the fresh and hardened properties of self-compacting concrete (SCC) with accumulation of metakaolin (MK). Soorh used as natural material which is calcined in an electric oven at 800Â Â°C for 2Â h to obtain metakaolin. A total of five mixtures have been developed, including varying MK contents (0â20 by weight of cement) and a water / binder ratio (W / B) of 0.38. The fresh properties were explored by slump flow, T50 flow, V-funnel, L-box, J-Ring sieve segregation test. Moreover, the hardened properties of concrete were performed for compressive, splitting tensile and flexural strength and permeability of SCC mixtures. The fresh concrete test results show that even if no viscosity modifier is required, satisfactory fresh concrete properties of SCC can be obtained by replacing the local MK content. At 15 replacement of cement with metakaolin maximum compressive, tensile and flexural strength is observed which is 10.39, 10.19 and 7.07 more than that of control mix, respectively, and maximum reduction in water penetration depth which is 34 less than that of control mix is observed at 28Â days age. It can be concluded from this study that 15 replacement of cement with local metakaolin is optimum. Â© 2021, Springer Nature Switzerland AG.